Rhabdomyosarcoma of the head and neck in children - Radzikowska, Joanna; Kukwa, Wojciech; Kukwa, Andrzej; Czarnecka, Anna; Krzeski, Antoni (Contemporary Oncology/Współczesna Onkologia, 2015)
Rhabdomyosarcoma (RMS) is the most frequent soft tissue sarcoma in children. It is localized in the head and neck region in 40% of cases. Treatment of RMS is complex, including multi-drug chemotherapy, radiotherapy and surgery. The progress that has been accomplished in oncology in recent decades significantly improved outcomes. The 5-year survival rate raised from 25% in 1970 to 73% in 2001, according to IRS-IV data. The outcome is influenced by primary tumor localization, clinical staging, histological tumor type and age at the moment of diagnosis. The relatively rare incidence of these tumors resulted in difficulties in creating more standardized therapeutic protocols. Comparison of outcomes in large patients groups led to an increase in the number of patients with complete remission. Although survival rates of RMS patients have improved, searching for new therapeutic modalities and substances is still essential to improve outcomes in cases of more advanced stages and unfavorable tumor localizations.